The Raghupañcikā of Vallabhadeva Being the Earliest Commentary on the Raghuvaṃśa of Kālidāsa : Critical Edition and Notes Volume 2 - Desző, Csaba; Goodall, Dominic; Isaacson, Harunaga (Asian Studies E-Books Online, Collection 2025, 2025)
For more than a millennium, Kālidāsa's poem "Lineage of the Raghus" ( Raghuvaṃśa ) has been acknowledged as one of the masterpieces of Sanskrit literature. Thousands of manuscripts transmit it, and dozens of pre-modern commentaries expound the text. This is the second volume (out of three) of the earliest surviving commentary, that of the tenth-century Kashmirian Vallabhadeva. The text that he had before him of Kālidāsa's poems differs in many places from that printed in other editions, which generally follow the readings of the commentator Mallinātha, who wrote four centuries later. Notes discuss the text and report the readings of three other hitherto unpublished commentaries that predate Mallinātha, namely those of Śrīnātha, Vaidyaśrīgarbha and Dakṣiṇāvartanātha.